Strategi branding sekolah PAUD dalam meningkatkan kesadaran masyarakat - Amalya, Meyfa Nur Alfu Laila (Maliki Interdisciplinary Journal, 2025)
The increasingly competitive landscape of early childhood education (PAUD) necessitates institutions to establish a strong identity and image. Branding is a crucial element in building positive perceptions in the eyes of the public, particularly parents, and attracting potential students. This article examines the significance of branding for PAUD schools and outlines strategic stages that can be implemented to enhance public awareness. Discussed strategies include designing unique school uniforms, establishing the institution’s positive characteristics and values, systematic efforts to improve students’ academic and non-academic achievements, optimizing visual and textual documentation with appealing designs, comprehensive utilization of information technology (covering website development, social media usage, publishing online blogs/articles, and developing school applications), formulating effective slogans or taglines, and fostering alumni networks and developing valuable alumni profiles. This article is written using a literature review method, analyzing various relevant sources such as scientific journals, articles, and books. The purpose is to provide a comprehensive view on PAUD school branding strategies as a proactive effort to win competition, build public trust, and ultimately support the improvement of early childhood education quality.